Role Playing Methods to Improve Children's Oral Language Skills - Mayolanda Hesti; Raras Gita Atika (Universitas Negeri Padang, 2019)
Children are the next generation of the nation for that as the next generation of educators or parents need to prepare children from an early age. One of them through early childhood education. various types of education that can be used in early childhood education, namely formal education and non-formal education. Education not only develops knowledge but also develops character abilities in children, including the ability to socialize and express opinions verbally is an ability that must be developed in children. One method of learning that is able to develop children's oral speaking and socializing skills is by playing roles.Keywords: Role Playing Method, Oral Language Skills, Early Childhood